Update on Tumors of Adrenal Medulla and Extra-adrenal Paraganglia. Issue 5 (September 2017) - Kimura, Noriko
Abstract : Abstract: Tumors of the adrenal medulla and extra-adrenal paraganglia are discussed in the chapter separate from tumors of the adrenal cortex in the fourth edition of the World Health Organization Classification of Tumors of Endocrine Organs. The neuroblastic tumors have been included in this chapter for the first time. Adrenal medulla, extra-adrenal paraganglia, and neuroblasts are derived from the neural crest and are distributed in the adrenal gland and extra-adrenal regions; tumors of these cells are intimately related to each other, with similar morphology, catecholamine production, biological behavior, and tumorigenesis. One of the important updates in the new edition are changes in the terminology of pheochromocytoma (PCC) and paraganglioma (PGL). The current understanding is that all PCCs and PGLs have some metastatic potential; therefore, the categories of benign and malignant PCC and PGL, previously included in the 2004 World Health Organization Classification, have been eliminated and replaced by only "pheochromocytoma" or "paraganglioma, " in favor of an approach based on risk stratification. In addition, new genetic discoveries have profoundly altered our understanding of PCC and PGL. At least 30% of these tumors are now known to be hereditary, and genotype-phenotype correlations determine tumor location, catecholamine production, multiplicity, risk of metastasis, and syndromic associations. New information on genetic alterations and their clinical significance in PCCs and PGLs is discussed in this chapter.